Biological Basis of Tree-Ring Formation: A Crash Course - Rathgeber, Cyrille B. K.; Cuny, Henri E.; Fonti, Patrick (Frontiers in Plant Science, 2016)
Wood is of crucial importance for man and biosphere. In this mini review, we present the fundamental processes involved in tree-ring formation and intra-annual dynamics of cambial activity, along with the influences of the environmental factors. During wood formation, new xylem cells produced by the cambium are undergoing profound transformations, passing through successive differentiation stages, which enable them to perform their functions in trees. Xylem cell formation can be divided in five major phases: (1) the division of a cambial mother cell that creates a new cell; (2) the enlargement of this newly formed cell; (3) the deposition of its secondary wall; (4) the lignification of its cell wall; and finally, (5) its programmed cell death. In most regions of the world cambial activity follows a seasonal cycle. At the beginning of the growing season, when temperature increases, the cambium resumes activity, producing new xylem cells. These cells are disposed along radial files, and start their differentiation program according to their birth date, creating typical developmental strips in the forming xylem. The width of these strips smoothly changes along the growing season. Finally, when climatic conditions deteriorate (temperature or water availability in particular), cambial activity stops, soon followed by cell enlargement, and later on by secondary wall deposition. Without a clear understanding of the xylem formation process, it is not possible to comprehend how annual growth rings and typical wood structures are formed, recording seasonal variations of the environment as well as extreme climatic events.